Childbirth care in Brazil: a critical situation has not yet been overcome. 1999-2013 - Ana Lucia Andrade da Silva; Antonio da Cruz Gouveia Mendes; Gabriella Morais Duarte Miranda; Pedro Miguel dos Santos Neto
Abstract Objectives: to analyze the evolution of childbirth care in Brazil, between 1999-2013. Methods: a time-series ecological study, using data from Ministry of Health, Brazilian Institute of Geography and Statistics, and Interagency Network of Information for Health. 18 indicators were analyzed related to childbirth and mortality. Results: there was a reduction in rates of fertility, natality and the total number of births, with increased cesarean surgeries. Growth of prenatal consultation, intensive care beds and reduction of beds in obstetrics sector. The significant growth of caesarean deliveries, prenatal consultation coverage and concentration of births in hospitals occurred simultaneously with the growth: of preventable child deaths by adequate attention, management causes and appropriate delivery, prematurity; low weight; Down's syndrome; and the persistence of maternal deaths due to direct obstetric causes. Conclusions: persists hegemonic technocratic model of childbirth care without considering the observed changes in the profile of mothers and births, with slow reduction of perinatal and neonatal deaths and maintenance of high maternal mortality demonstrating that the critical situation of delivery care model in Brazil has not, yet, been overcome.